Isolation, Characterization, and In Vitro Evaluation of Bacteriophages for Controlling the Fish Pathogen Aeromonas hydrophila - Nasri Julaini; Dinamella Wahjuningrum; Widanarni; Sukenda (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract   Highlight Research 1. A lytic bacteriophage was successfully isolated from catfish pond water in Dramaga, Bogor, with a high density of 5.68 × 10⁹ PFU/mL. 2. Characterization revealed round to irregular plaque morphology with high clarity and diameters reaching 0.35 cm. 3. The bacteriophage exhibited high host specificity, being effective only against the A. hydrophila AH03 isolate from the AAHL collection. 4. Treatment at MOI 10 resulted in more effective inhibition of A. hydrophila growth compared to other treatments.   Abstract Aquaculture plays a vital role in global protein supply, yet its increasing production faces disease-related challenges, particularly A. hydrophila infections. This pathogen causes Motile Aeromonas Septicemia (MAS), leading to mass mortality in catfish and significant economic losses. While antibiotics have been the primary solution, their use is now restricted due to antimicrobial resistance, necessitating safe and sustainable alternatives. Phage have emerged as environmentally friendly, specific biocontrol agents to combat such infections. This study aimed to evaluate the effectiveness of lytic phage in controlling the fish pathogen A. hydrophila through an in vitro approach. The research stages included phage isolation (density assay), characterization (plaque morphology and host range testing), and evaluation of phage against A. hydrophila (bacteriolytic efficacy assay). A completely randomized design was employed, with six treatments and three replicates, media control (K-), A. hydrophila control (K+), antibiotic control (enrofloxacin 0.1 mg/mL, KA), and phage treatments at multiplicities of infection (MOI) of 0.1, 1, and 10 (P0.1, P1, P10) for the bacteriolytic efficacy assay. Phage isolated from catfish ponds in Dramaga, Bogor, exhibited a high titer (5.68 × 10⁹ PFU/mL) and formed clear, round plaques (0.17-0.35 cm diameter). They demonstrated a narrow host range, lysing only 1 of 10 A. hydrophila isolates. In efficacy assays, phage treatment at an MOI of 10 significantly reduced bacterial density (p < 0.05) at 24 hours post infection, decreasing the OD 600 nm by 38.7% compared to the positive control. These results indicate the potential of these phage as an antibiotic alternative for controlling A. hydrophila in aquaculture.